Genome-Wide Association Study for Body Length, Body Height, and Total Teat Number in Large White Pigs - Hong, Yifeng; Ye, Jian; Dong, Linsong; Li, Yalan; Yan, Limin; Cai, Gengyuan; Liu, Dewu; Tan, Cheng; Wu, Zhenfang (Frontiers in Genetics, 2021)
Body length, body height, and total teat number are economically important traits in the pig industry, as these traits are usually associated with the growth, reproductivity and longevity potential of piglets. To explore the genetic correlation between these traits and identify candidate genes for these traits, a total of 2,068 Large White pigs were collected and genotyped. We estimated the heritability of body length, body height, and total teat number were 0.25  0.04, 0.11  0.03, and 0.22  0.04, respectively. The genetic correlation between body length and body height was 0.63  0.15, and there was no genetic correlation among those traits. We used two method, including single-locus and weighted single step to perform genome-wide association studies (GWAS). Getting 195,895 high-quality single nucleotide polymorphisms through genotyping by sequencing technology. In total, 76, 13, and 29 significant SNPs were detected by single-locus GWAS in body length, body height, and total teat number traits. Notably, the top SNP (S17_15781294) explained 9.09% genetic variance of body length traits, this SNP also explained 9.57% genetic variance of body height. Most of quantitative trait locus area were detected by single-locus and weighted single step GWAS. Results of GWAS for the three important agricultural traits identified a series of candidate genes, such as BMP2 for body length and body height, PLCB1 for body length, SSC14: 128.29–128.86 Mb for body length and body height, and ABCD4 for total teat number, providing a starting point for further inheritance research. These findings reveal the complexity of the genetic mechanism of the three traits and provide guidance for subsequent genetic improvement through genome selection